Crystal Structures of the Global Regulator DasR from Streptomyces coelicolor: Implications for the Allosteric Regulation of GntR/HutC Repressors. - Fillenberg, Simon; Frieß, Mario; Körner, Samuel; Böckmann, Rainer; Muller, Yves (PLoS ONE, 2016)
Small molecule effectors regulate gene transcription in bacteria by altering the DNA-binding affinities of specific repressor proteins. Although the GntR proteins represent a large family of bacterial repressors, only little is known about the allosteric mechanism that enables their function. DasR from Streptomyces coelicolor belongs to the GntR/HutC subfamily and specifically recognises operators termed DasR-responsive elements (dre-sites). Its DNA-binding properties are modulated by phosphorylated sugars. Here, we present several crystal structures of DasR, namely of dimeric full-length DasR in the absence of any effector and of only the effector-binding domain (EBD) of DasR without effector or in complex with glucosamine-6-phosphate (GlcN-6-P) and N-acetylglucosamine-6-phosphate (GlcNAc-6-P). Together with molecular dynamics (MD) simulations and a comparison with other GntR/HutC family members these data allowed for a structural characterisation of the different functional states of DasR. Allostery in DasR and possibly in many other GntR/HutC family members is best described by a conformational selection model. In ligand-free DasR, an increased flexibility in the EBDs enables the attached DNA-binding domains (DBD) to sample a variety of different orientations and among these also a DNA-binding competent conformation. Effector binding to the EBDs of DasR significantly reorganises the atomic structure of the latter. However, rather than locking the orientation of the DBDs, the effector-induced formation of β-strand β* in the DBD-EBD-linker segment merely appears to take the DBDs 'on a shorter leash' thereby impeding the 'downwards' positioning of the DBDs that is necessary for a concerted binding of two DBDs of DasR to operator DNA.

Structural Model of the mIgM B-Cell Receptor Transmembrane Domain From Self-Association Molecular Dynamics Simulations - Frieß, Mario; Pluhackova, Kristyna; Böckmann, Rainer (Frontiers in Immunology, 2018)
Antigen binding to B-cell antigen receptors (BCRs) followed by signaling initiates the humoral immune response. The signaling is intimately coupled to nanoclustering of BCRs and their sorting to specific membrane domains, a process that is ruled by interactions between the BCR transmembrane domain and lipids. While the structure of the extracellular domains of BCRs has been resolved, little is known about the configuration of the constituting four immunoglobulin domains spanning the membrane. Here, we modeled the structure of the transmembrane (TM) domain of the IgM B-cell receptor using self-assembly coarse-grained molecular dynamics simulations. The obtained quaternary structure was validated against available experimental data and atomistic simulations. The IgM-BCR-TM domain configuration shows a 1:1 stoichiometry between the homodimeric membrane-bound domain of IgM (mIgM) and a Ig-alpha/Ig-beta heterodimer. The mIgM homodimer is based on an asymmetric association of two mIgM domains. We show that a specific site of the Ig-alpha/Ig-beta heterodimer is responsible for the association of IgM-BCRs with lipid rafts. Our results further suggest that this site is blocked in small-sized IgM-BCR clusters. The BCR TM structure provides a molecular basis for the previously suggested dissociation activation model of B-cell receptors. Self-assembly molecular dynamics simulations at the coarse-grained scale here proved as a versatile tool in the study of receptor complexes.
Keywords: B-cell receptor; transmembrane domain; nanodomains; self-assembly; molecular dynamics simulations; coarse-grained simulations; dissociation activation model